The Effectiveness of the Absentee Ownership Ban in Supporting National Food Security - Soediro, Soediro; Muhammad, Mahdi (Faculty of Law, Universitas Pattimura, 2026)
Introduction: Agricultural land constitutes a strategic foundation for national food security and food sovereignty. However, absentee ownership—where land is held by individuals who neither reside near nor actively cultivate it—continues to weaken agricultural productivity and distort land governance. Although the Basic Agrarian Law formally prohibits such practices, structural and normative deficiencies hinder effective enforcement.Purposes of the Research: This study aims to analyze the effectiveness of absentee ownership prohibition regulations and formulate policy recommendations to improve their implementation in order to support food security.Methods of the Research: The research employs a normative juridical (doctrinal) method focusing on positive legal norms governing absentee land ownership. It utilizes statutory, conceptual, and public policy approaches to assess regulatory coherence, enforcement limitations, and the need for reform, particularly in strengthening agrarian governance and its integration with national food policy frameworks.Findings of the Research: The findings demonstrate that the existing regulatory regime remains weak in supervision, operational definitions of active management, progressive sanctioning mechanisms, and integration with sustainable agricultural land protection policies. This study advances agrarian scholarship by repositioning the expansion of the absentee prohibition as a strategic governance instrument directly linked to land productivity, sustainable utilization, and national food security enhancement. This research offers a new perspective by integrating the prohibition of absentee ownership into a comprehensive food security policy framework, which has not been widely explored in the literature.